When Actions Speak Louder Than Prospects - Loomes, Graham (American Economic Review, 1988)
Many theories of individual choice under risk and uncertainty are formu lated in terms of preferences over prospects, i.e., probability distr ibutions of consequences. By contrast, regret theory is formulated in terms of actions, i.e., n-tuples of state-contingent consequences. W hat appear from the viewpoint of prospect-based theories to be innocu ous rephrasings of choice problems are predicted by regret theory to cause people to reverse their choices. This paper follows up earlier results with a new kind of experimental test. The new evidence favors regret theory. Copyright 1988 by American Economic Association.